Metabonomics Study in Mice With Learning and Memory Impairment on the Intervention of Essential Oil Extracted From Cinnamomum camphora Chvar. Borneol - Tang, Yin; Lv, Xiaofan; Liu, Yumin; Cui, Donghong; Wu, Yani (Frontiers in Pharmacology, 2022)
Our objective was to explore the mechanism of essential oil that was extracted from Cinnamomum camphora chvar. Borneol (Borneol essential oil) for improving learning and memory impairment in mice. Brain tissue and plasma samples of a normal group, a model group, a Borneol essential oil group and a reference group were detected using gas chromatography time-of-flight mass spectrometry (GC-TOFMS) in order to find differential metabolites and analyze metabolic pathways. Results showed that there were 11 different metabolites –including glycine and azelaic acid –in plasma samples, and that there were 26 different metabolites–including adenine and aspartic acid –in brain tissue samples. These metabolites are involved in phenylalanine, tyrosine, and tryptophan biosynthesis, phenylalanine metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, beta-alanine metabolism, glyoxylate acid and dicarboxylate metabolism, and aminoacyl-tRNA biosynthesis. Thus, Borneol essential oil may improve learning and memory impairment by regulating amino acid metabolism and/or neurotransmitter changes.